Advances in the molecular understanding of G protein-coupled receptors and their future therapeutic opportunities - Daniel N. Obot; Godswill J. Udom; Anwanabasi E. Udoh; Nkechi J. Onyeukwu; Ayobami J. Olusola; Ikanke M. Udoh; Israel K. Umana; Omoniyi K. Yemitan; Jude E. Okokon (SpringerOpen, 2021)
Abstract Background Understanding the mechanisms, activated and inhibited pathways as well as other molecular targets involved in existing and emerging disease conditions provides useful insights into their proper diagnosis and treatment and aids drug discovery, development and production. G protein-coupled receptors (GPCRs) are one of the most important classes of targets for small-molecule drug discovery. Of all drug targets, GPCRs are the most studied, undoubtedly because of their pharmacological tractability and role in the pathophysiology as well as the pathogenesis of human diseases. Main body of the abstract GPCRs are regarded as the largest target class of the "druggable genome" representing approximately 19% of the currently available drug targets. They have long played a prominent role in drug discovery, such that as of this writing, 481 drugs (about 34% of all FDA-approved drugs) act on GPCRs. More than 320 therapeutic agents are currently under clinical trials, of which a significant percentage targets novel GPCRs. GPCRs are implicated in a wide variety of diseases including CNS disorders, inflammatory diseases such as rheumatoid arthritis and Crohn's disease, as well as metabolic disease and cancer. The non-olfactory human GPCRs yet to be clinically explored or tried are endowed with perhaps a huge untapped potential drug discovery especially in the field of immunology and genetics. Short conclusion This review discusses the recent advances in the molecular pharmacology and future opportunities for targeting GPCRs with a view to drug development.